Analisis Distribusi Persentase Pareto Kualitas Stok pada Jaringan Apotek Kimia Farma di Sulawesi Tenggara Tahun 2024 : Optimalisasi Manajemen Persediaan Berbasis ABC Analysis - Faisal Faisal; Irman Idrus (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
This study aims to analyze the Pareto distribution of stock quality in 16 Apotek Kimia Farma outlets in Southeast Sulawesi during the period of January to October 2024, with a focus on inventory management based on ABC analysis. The research employed a descriptive quantitative design with a longitudinal (time series) approach, involving descriptive, trend, comparative, and correlation analyses to evaluate stock distribution and its stability. The findings show that, overall, the stock distribution in Kimia Farma outlets follows the Pareto principle, with category A accounting for an average of 73-86% of total sales value. However, significant variations were found across outlets, with outlets such as KF 004 and KF Hasanuddin Kendari showing high stability in category A distribution, while outlets like KF BULOG and KF Kolaka exhibited greater fluctuations. Seasonal patterns were also identified, with a decrease in category A percentages in April-May and October. Based on these findings, optimizing inventory management strategies based on Pareto distribution can enhance stock management efficiency, with recommendations to focus on category A, conduct regular evaluations of categories B and C, and adjust for seasonal patterns. This study suggests the implementation of more flexible inventory management strategies for each outlet to improve operational efficiency and customer service.